Impact strength of composites with nano-enhanced resin after fire exposure - Reis, P.N.B.; Ferreira, J.A.M.; Zhang, Z.Y.; Benameur, T.; Richardson, M.O.W. (Composites. Part B, Engineering, 2014)
Composite materials have been widely used in several engineering applications. However, there are very few studies about the effects of nanoclays on the impact strength of laminates after exposure to the fire. Therefore, this paper intends to study this subject and the impact performance was analysed by low velocity impact tests carried out at different incident impact energy levels. For better dispersion and interface adhesion matrix/clay, nanoclays were previously subjected to a silane treatment appropriate to the epoxy resin. The exposure to the fire decreases the maximum load and increases the displacement in comparison with the respective values obtained at room temperature. Mathematical relationships are proposed to estimate the maximum impact force and displacement, based on the total impact energy and flexural stiffness. Finally, a decrease of the elastic recuperation can be found, independently of the benefits introduced by the nanoclays.